2018
DOI: 10.1109/twc.2018.2822801
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Transmission of Big Data: A Transmission Time Analysis Over Fading Channel

Abstract: In this paper, we investigate the transmission time of a large amount of data over fading wireless channel with adaptive modulation and coding (AMC). Unlike traditional transmission systems, where the transmission time of a fixed amount of data is typically regarded as a constant, the transmission time with AMC becomes a random variable, as the transmission rate varies with the fading channel condition. To facilitate the design and optimization of wireless transmission schemes for big data applications, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In fact, the temporal variations of the fading channels are characterized by the second order statistics, in particular, the level crossing rate (LCR) and the AOD. These two important statistics are useful for the Markov modeling of wireless channels [2]- [3] and the design of error control codes and the type of diversity to be used in wireless communication systems to combat the effect of fading, and therefore they have been the topic of many works in the literature. Since it can change with time because of user mobility, fading can be represented as a random process.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the temporal variations of the fading channels are characterized by the second order statistics, in particular, the level crossing rate (LCR) and the AOD. These two important statistics are useful for the Markov modeling of wireless channels [2]- [3] and the design of error control codes and the type of diversity to be used in wireless communication systems to combat the effect of fading, and therefore they have been the topic of many works in the literature. Since it can change with time because of user mobility, fading can be represented as a random process.…”
Section: Introductionmentioning
confidence: 99%
“…An initial investigation on the transmission time of big data with discrete rate adaptation over fading channels has been recently reported [9].…”
Section: Further Applicationsmentioning
confidence: 99%
“…When the transmission sessions are short, the quality of service experienced by individual sessions vary dramatically around the average. In particular, it was recently shown that the transmission time of a fixed amount of data with adaptive transmission over fading channels vary considerably around its average [9]. With the growing popularity of IoT devices and big data applications, future wireless systems need to support increasing number of short transmission sessions, initiated for example by sensor nodes.…”
Section: Introductionmentioning
confidence: 99%